Efferocytosis: the resolution of inflammation in cardiovascular and cerebrovascular disease - Zhang, Bingtao; Zou, Yan; Yuan, Zixuan; Jiang, Kun; Zhang, Zhaoxiang; Chen, Shujuan; Zhou, Xiaoming; Wu, Qi; Zhang, Xin (Frontiers in Immunology, 2024)
Cardiovascular and cerebrovascular diseases have surpassed cancer as significant global health challenges, which mainly include atherosclerosis, myocardial infarction, hemorrhagic stroke and ischemia stroke. The inflammatory response immediately following these diseases profoundly impacts patient prognosis and recovery. Efficient resolution of inflammation is crucial not only for halting the inflammatory process but also for restoring tissue homeostasis. Efferocytosis, the phagocytic clearance of dying cells by phagocytes, especially microglia and macrophages, plays a critical role in this resolution process. Upon tissue injury, phagocytes are recruited to the site of damage where they engulf and clear dying cells through efferocytosis. Efferocytosis suppresses the secretion of pro-inflammatory cytokines, stimulates the production of anti-inflammatory cytokines, modulates the phenotype of microglia and macrophages, accelerates the resolution of inflammation, and promotes tissue repair. It involves three main stages: recognition, engulfment, and degradation of dying cells. Optimal removal of apoptotic cargo by phagocytes requires finely tuned machinery and associated modifications. Key molecules in efferocytosis, such as ‘Find-me signals’, ‘Eat-me signals’, and ‘Don’t eat-me signals’, have been shown to enhance efferocytosis following cardiovascular and cerebrovascular diseases. Moreover, various additional molecules, pathways, and mitochondrial metabolic processes have been identified to enhance prognosis and outcomes via efferocytosis in diverse experimental models. Impaired efferocytosis can lead to inflammation-associated pathologies and prolonged recovery periods. Therefore, this review consolidates current understanding of efferocytosis mechanisms and its application in cardiovascular and cerebrovascular diseases, proposing future research directions.